Integrating EUCS and TAM to Evaluate DAPODIK User Satisfaction and Use in Central Lombok - Melyana Febrian; Khairul Imtihan; Sofiansyah Fadli (Journal of Information System and Informatics, 2026)
This study evaluates user satisfaction and post-adoption behavior toward the Data Pokok Pendidikan (DAPODIK) Information System by integrating the End-User Computing Satisfaction (EUCS) and Technology Acceptance Model (TAM) within a mandatory public education system context. Although DAPODIK has been nationally enforced and widely implemented in Indonesia, empirical evidence explaining how system quality translates into user satisfaction, technology acceptance, and actual use remains limited, particularly at the local government level. A quantitative survey-based approach was employed involving 255 active DAPODIK users in Central Lombok Regency, Indonesia, collected between December 2025 and January 2026 using a five-point Likert-scale questionnaire. Data were analyzed using PLS-SEM, encompassing measurement model evaluation, structural model assessment, hypothesis testing, and moderation analysis of digital literacy. The findings indicate that format, ease of use, and timeliness significantly influence user satisfaction, whereas content and accuracy do not show significant effects. User satisfaction has a strong positive effect on perceived usefulness and perceived ease of use, while behavioral intention significantly predicts actual system use. The moderation analysis further reveals that digital literacy strengthens the relationship between technology acceptance and users’ attitudes toward system use. From a practical perspective, the results suggest that policymakers should prioritize interface format, usability simplification, and system responsiveness during data collection cycles to enhance user satisfaction and sustained system use.